The association between social capital and HIV treatment outcomes in South Africa. - Grace Musanse Mukoswa; Salome Charalambous; Gill Nelson (PLoS ONE, 2017)
HIV treatment has reduced morbidity and mortality. By 2012, it was estimated that 60.4% of eligible South Africans accessed antiretroviral treatment; however, treatment adherence and retention remain the greatest challenges. There is a growing belief that social capital, seen as "the features of social organization that facilitate cooperation for mutual benefit", is important in promoting HIV treatment retention. The aim of this study was to establish whether social capital is associated with HIV treatment outcomes.This was a cross-sectional analysis of data from a cohort study that investigated how patient outcomes were linked to clinical characteristics, and included exploratory factor and logistic regression analysis. Data from 943 patients were analyzed. Outcomes for the analysis were visit non-adherence, unsuppressed viral load, and treatment failure. Sixteen percent of patients (n = 118) had unsuppressed viral loads; 19% (n = 179) were non-adherent; and 32% (n = 302) experienced treatment failure. Social capital had two dimensions that were described by two factors. There was no association between either factor and visit non-adherence. Social capital factor 1 was marginally associated with lower risks of unsuppressed viral load and treatment failure at 12 months (OR = 0.78; 95% CI = 0.58-1.03 and OR = 0.76; 95% CI = 0.62-0.93, respectively); but not with visit non-adherence (OR = 0.93; 95% CI = 0.71-1.22). After controlling for confounders, the odds of both unsuppressed viral load and treatment failure decreased with an increase in social capital factor 1.This study suggests that social capital, in terms of the number of groups to which an HIV-infected person belongs, the diversity of the groups, availability of child support, and time available for community projects, is protective against poor HIV treatment outcomes. Implementers and policy makers in the areas of HIV treatment and prevention need to consider the inclusion of social capital in the design of HIV/AIDS treatment program.